2012
DOI: 10.1371/journal.pone.0033395
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-Mediated Control of HLA-G Expression and Function

Abstract: HLA-G is a non-classical HLA class-Ib molecule expressed mainly by the extravillous cytotrophoblasts (EVT) of the placenta. The expression of HLA-G on these fetal cells protects the EVT cells from immune rejection and is therefore important for a healthy pregnancy. The mechanisms controlling HLA-G expression are largely unknown. Here we demonstrate that miR-148a and miR-152 down-regulate HLA-G expression by binding its 3′UTR and that this down-regulation of HLA-G affects LILRB1 recognition and consequently, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 35 publications
4
108
0
Order By: Relevance
“…69 In addition, NK cell-mediated cytolysis was increased by overexpression of miR-152 69 and the downregulation of HLA-G-affected LILRB1 (inhibitory receptor) recognition, which resulted in enhanced killing activity of NK cells. 68 These studies further suggest a major role for miR-152 in mediating immune responses. In a more recent study, activated CD4 1 T lymphocytes cultured in the presence or absence of HLA-G were screened for 87 miRNAs and it was found that miR-451 and miR-210 were modulated by soluble HLA-G. 70 The interaction between miR-148 and HLA-C has been reported in studies of HIV infection.…”
Section: Micrornas and Immune Cells At The Maternal-fetal Interfacementioning
confidence: 85%
See 1 more Smart Citation
“…69 In addition, NK cell-mediated cytolysis was increased by overexpression of miR-152 69 and the downregulation of HLA-G-affected LILRB1 (inhibitory receptor) recognition, which resulted in enhanced killing activity of NK cells. 68 These studies further suggest a major role for miR-152 in mediating immune responses. In a more recent study, activated CD4 1 T lymphocytes cultured in the presence or absence of HLA-G were screened for 87 miRNAs and it was found that miR-451 and miR-210 were modulated by soluble HLA-G. 70 The interaction between miR-148 and HLA-C has been reported in studies of HIV infection.…”
Section: Micrornas and Immune Cells At The Maternal-fetal Interfacementioning
confidence: 85%
“…However, it had previously been demonstrated in the context of pregnancy that HLA-G expressed mainly by the extravillous trophoblasts of the placenta could be downregulated by miR-148a and miR-152 by binding to its 39-untranslated region. 68 Similarly miR-152 has been shown to repress HLA-G without affecting the invasiveness of JEG-3 choriocarcinoma cells. 69 In addition, NK cell-mediated cytolysis was increased by overexpression of miR-152 69 and the downregulation of HLA-G-affected LILRB1 (inhibitory receptor) recognition, which resulted in enhanced killing activity of NK cells.…”
Section: Micrornas and Immune Cells At The Maternal-fetal Interfacementioning
confidence: 99%
“…This region consist of 2-7 nucleotides that are perfectly complementary to that of the mRNA. The seed region of miR-148a and miR-148b is the same and the predicted binding energies are similar (Manaster et al, 2012;Tan et al, 2007). Therefore it is thought that these two miRNAs have similar activity.…”
Section: Mir-148a Mir-148b and Mir-152 Expressionmentioning
confidence: 88%
“…These are: miR-148a, miR-148b and miR-152 (Tan et al, 2007). It has been shown that both miR148a and miR-152 can downregulate the expression of HLA-G and reduce the binding of the inhibitory receptor ILT2 to HLA-G cells (Manaster et al, 2012;Zhu et al, 2010). As a consequence, NK cell-mediated cytotoxicity is increased.…”
Section: Micrornasmentioning
confidence: 99%
“…The miRNA regulation of MHC class I has been previously characterized in HLA-C and HLA-G, which are controlled by miR148a and miR-152, respectively (45,46). However, the duck UDA transcript is not a target of either miR-148a or miR-152.…”
Section: Uda Is Regulated By the Let-7 Mirna Familymentioning
confidence: 99%